Leadership in innovation communities: The impact of transformational leadership language on member participation. Issue 3 (21st July 2021) - Becker, Laura; Coussement, Kristof; Büttgen, Marion; Weber, Ellen
Abstract: Many organizations seek to establish online innovation communities (ICs) to obtain valuable knowledge and innovative ideas, though both research and practice suggest that they also struggle to sustain continued, high‐quality member participation. Designated IC moderators might be able to stimulate IC members to participate regularly and make high‐quality contributions. In response to calls to integrate organizational behavior and IC research, this study addresses the impact of community moderators' uses of transformational leadership (TFL) language on member participation. By operationalizing the TFL dimensions—charisma, individualized consideration, and intellectual stimulation—with language cues, this article uses an automated text analysis approach to review 64 firm‐hosted ICs with 538, 805 posts, analyzed with two hierarchical linear models. The findings show that moderators' charismatic language cues enhance members' participation quality and quantity. Although individualized consideration and intellectual stimulation increase participation quality, they decrease participation quantity. Organizations thus should assign moderators to lead ICs by using TFL language strategically, in accordance with the focal IC goals, in terms of the quality and quantity of member contributions to their innovation processes. This article contributes to the literature by exploring how leadership language in online communities can facilitate the development of innovative ideas. In addition, this study offers a more nuanced view on the effects of TFL by revealing both positive and negative outcomes in firm‐hosted online ICs and it introduces a new, objective measure of TFL built on linguistic markers. This article also includes specific guidelines for how moderators can achieve effective leadership through their language use, as well as managerial implications for the effective selection, training, and support of IC moderators.